The last crusade : the epic voyages of Vasco da Gama - Cliff, Nigel; Cliff, Nigel (New York, N.Y. : Atlantik Book, 2012)
In 1498 a young captain named Vasco da Gama sailed from Portugal, circumnavigated Africa, crossed the Indian Ocean, and discovered the sea route to the Indies and, with it, access to the fabled wealth of the East. It was the longest voyage ever undertaken at that time. With blood-red Crusader crosses emblazoned on their sails, the explorers arrived in the heart of the Muslim East in an era when the old hostilities between Christianity and Islam had risen to a new level of intensity. In two voyages that spanned six years, da Gama would fight a running sea battle that would ultimately change the fate of three continents.
Includes bibliographical references (p. [512]-526) and index.
Keywords: Gama, Vasco da, -- 1469-1524.; Gama, Vasco da, -- 1469-1524 -- Influence; East and West; Christianity and other religions -- Islam -- History -- 16th century; Islam -- Relations -- Christianity -- History -- 16th century; Africa -- Discovery and exploration -- Portuguese; India -- Discovery and exploration -- Portuguese; Africa -- Discovery and exploration -- Religious aspects; India -- Discovery and exploration -- Religious aspects